PERAN KOMUNIKASI DALAM STRATEGI PENGEMBANGAN UMKM DI MEDAN UNTUK MENINGKATKAN DAYA SAING PASAR LOKAL. - sitepu, Jupianus; Susanto, Darma; Sukatendel, Rahel; Situmorang, Maria Kristina (JURNAL REGIONOMIC, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, especially in terms of creating jobs and driving economic growth at the local level. However, MSMEs in Medan City face a number of challenges that hinder their ability to compete in the local market. These constraints include limitations in business management, underdeveloped marketing, and lack of product innovation and technology utilization. This study aims to identify various factors affecting the competitiveness of MSMEs in Medan City and formulate development strategies that can be realized to improve it. The method used in this research is a qualitative approach through in-depth interviews and participatory observation. The findings of this study indicate that managerial capacity building, implementation of digital marketing strategies, product innovation, and use of technology can be effective strategic measures in improving the competitiveness of MSMEs in Medan City. It is expected that the results of this study can provide useful recommendations for MSME actors as well as the government in formulating policies that support the development of MSMEs in Medan City.